2004
DOI: 10.1046/j.1529-8817.2003.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and population genetics of the ALDH2 locus: random genetic drift, selection, and low levels of recombination

Abstract: SummaryThe catalytic deficiency of human aldehyde dehydrogenase 2 (ALDH2) is caused by a nucleotide substitution (G1510A; Glu487Lys) in exon 12 of the ALDH2 locus. This SNP, and four non-coding SNPs, including one in the promoter, span 40 kb of ALDH2; these and one downstream STRP have been tested in 37 worldwide populations. Only four major SNP-defined haplotypes account for almost all chromosomes in all populations. A fifth haplotype harbours the functional variant and is only found in East Asians. Though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
114
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 49 publications
8
114
0
4
Order By: Relevance
“…The present study confirmed that no variants of ALDH2 were detectable in the Caucasian population described in a previous study 33) . It is noteworthy that the Glu487Lys variant is almost exclusively present in East Asians, but its selective presence is puzzling.…”
Section: Discussionsupporting
confidence: 80%
“…The present study confirmed that no variants of ALDH2 were detectable in the Caucasian population described in a previous study 33) . It is noteworthy that the Glu487Lys variant is almost exclusively present in East Asians, but its selective presence is puzzling.…”
Section: Discussionsupporting
confidence: 80%
“…5). the SNP (rs886205) in exon 1 of the ALDH2 gene (F ST =0.500 in our calculation), which is known to have significantly different allele frequencies between Asians and Caucasians, probably because of natural selection [Oota et al, 2004]. At least part of the high-F ST SNPs we found here should also be in the loci under selection during local adaptation.…”
Section: Intra-and Interpopulation Comparison Of Allele Frequenciesmentioning
confidence: 82%
“…Some characteristics of the regions with respect to SNP density and spectrum of base changes have been observed. Comparisons of allele frequencies in this database and those in the public databases revealed that frequencies can differ widely between ethnic groups, possibly as a result of differential selection, as in the case of the aldehyde dehydrogenase 2 (ALDH2; MIM# 100650) (Oota et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests population variation in expression of genes coding for alcohol dehydrogenase and aldehyde dehydrogenase, enzymes involved in alcohol metabolism. Unique alleles and haplotypes occur in East Asians, which, after alcohol consumption, lead to characteristically high levels of toxic acetaldehyde and facial flushing (Oota et al 2004). It might therefore be expected that the power of alcohol to evoke NVP is particularly marked in East Asian populations.…”
Section: Discussionmentioning
confidence: 99%